TLR4 Deters Perfusion Recovery and Upregulates Toll-like Receptor 2 (TLR2) in Ischemic Skeletal Muscle and Endothelial Cells - Xu, Jia (Mol Med, 2015)
Toll-like receptors (TLRs) play an important role in regulating muscle regeneration and angiogenesis in response to ischemia. TLR2 knockout mice exhibit pronounced skeletal muscle necrosis and abnormal vessel architecture after femoral artery ligation, suggesting that TLR2 signaling is protective during ischemia. TLR4, an important receptor in inflammatory signaling, has been shown to regulate TLR2 expression in other systems. We hypothesize that a similar relationship between TLR4 and TLR2 may exist in hindlimb ischemia in which TLR4 upregulates TLR2, a mediator of angiogenesis and perfusion recovery. We examined the expression of TLR2 in unstimulated and in TLR-agonist treated endothelial cells (ECs). TLR2 expression (low in control ECs) was upregulated by lipopolysaccharide, the danger signal high mobility group box-1, and hypoxia in a TLR4-dependent manner. Endothelial tube formation on Matrigel as well as EC permeability was assessed as in vitro measures of angiogenesis. Time-lapse imaging demonstrated that ECs lacking TLR4 formed more tubes, whereas TLR2 knockdown ECs exhibited attenuated tube formation. TLR2 also mediated EC permeability, an initial step during angiogenesis, in response to high-mobility group box-1 (HMGB1) that is released by cells during hypoxic injury. In vivo, ischemia-induced upregulation of TLR2 required intact TLR4 signaling that mediated systemic inflammation, as measured by local and systemic IL-6 levels. Similar to our in vitro findings, vascular density and limb perfusion were both enhanced in the absence of TLR4 signaling, but not if TLR2 was deleted. These findings indicate that TLR2, in the absence of TLR4, improves angiogenesis and perfusion recovery in response to ischemia.